The EMU and the Spanish term structure of interest rates - Margarita Payeras (European Regional Science Association (ERSA), 1998)
Since the Spanish Government passed the "Central Bank Independence Law", The Sasp Spanish Central Bank, in order to form part of the European Central Bank (ECB) in the future EMU, has recently changed its monetary policy framework. Nowadays the Spanish policy monetary authority has an especific and main duty: :succeed in maintaining the prices under control. From then on, the term structure of interest rates (TSIR) is an important indicator of future inflation as well as a key variable to understand the transmission mechanism of monetary policy. So, the study of the term structure of interest rates has became an especially and lively topic for economists. The growing importance of the TSIR has demanded our attention. The main aim of this work is to analyse if the Spanish TSIR is determined by the foreign term structure.In order to , the study has structured as follows: in the 1st. section the concept and importance of TS are introduced; in the 2nd. throug a set of indicators, it is demonstrated that the Spanish capital market , engaged in a EMU project, presents a high degree of linking with other capital markets, especially with european capital markets. The 4th. section is devoted to test statiscally the hypothesis , based on the Exogenesi theory, that the Spanish TSIR is determined, in large measure by the German term structure. Finally, in the last section the main conclusions. are presented.
Keywords: 330